Unveiling the Role of Fractionated Graphene Oxide in Nitric Oxide Scavenging - Grigoriy R. Chermashentsev; Ivan V. Mikheev; Daria-Mariia V. Ratova; Elena V. Proskurnina; Mikhail A. Proskurnin (Molecules)
The feasibility of saturating aqueous anoxic solutions with in situ-generated high-purity nitric oxide (NO) is shown herein. A methemoglobin assay estimated the average nitric oxide concentration to be ca. 20 ± 3 µM. Graphene oxide aqueous dispersions were prepared by ultrasound-assisted extra exfoliation. These dispersions, including unpurified (pristine) samples and samples purified from transition metal impurities (bulk) fractions (bulkGO) and (nano) separated fractions (nanoGO) in a range of 0.5 to 14 kDa were prepared with ppm level concentrations. A robust and reproducible chemiluminescence (CL) assay validated the interaction between graphene oxide and NO in a luminol-based system. The results showed a significant increase in NO scavenging activity within the bulkGO fractions to nanofractions ranging from 14 to 3.5 kDa. The different reaction pathways underlying the transformation of nitric oxide are being evaluated, focusing on understanding how its presence or absence affects these processes. Our kinetic model suggests a significant difference in nitric oxide regulation; nanoGO demonstrates an interception rate seventy-times higher than that achieved through CL quenching.